Violence Situation, Speciality, Politics, and Storytelling - Wästerfors, David (Routledge Studies in Crime and Society, 2023)
This book considers how the concept of violence has been interpreted, used, defined, and explored by social researchers and thinkers. It does not provide a final answer to the question of what violence is or how it should be explained (or prevented), and instead offers a variety of useful ways of thinking about and theorising the phenomenon, mainly from a sociological standpoint. It outlines four ways of understanding violence: • Violence as situation: the tension that exists between category-driven and situational explanations. • Violence as speciality: the study of particularly violent actors, and how they may be understood by reference to childhood histories, technologies, institutions, culture, class, and gender. • Violence as politics: political violence and violent politics. • Violence as storytelling: representations of violence from a narrative perspective. Concluding with reflections on possible convergences between the four approaches and new directions for research, this book offers a unique and experimental approach to discussing and reconstructing the concept of violence. It is essential reading for criminologists, sociologists, and philosophers alike.